Increase students’s self-acceptance through cognitive restructuring techniques in group counseling - Filda, Widia; Hikmah, Nurul (Journal of Advanced Guidance and Counseling, 2023)
Purpose – Psychological problems that occur can be caused by the inability to understand and accept themselves properly. The purpose of this study is to describe descriptively the strategy of increasing students’ self-acceptance through group counseling with cognitive restructuring techniques.Method - Using a qualitative approach, with observation and interviews as data collection techniques. Subjects were selected using purposive sampling method with a total of 8 students. Analysis was carried out using the interaction method.Result  -  The results showed that the researcher as the key instrument applied group counseling through cognitive restructuring techniques consisting of six stages: rationalization strategies; identifying negative thoughts; introducing and practicing positive thoughts; diverting negative thoughts to positive thoughts; practice strengthening self-statements (homework); reflection and follow-up. Group counseling seeks to build connections based on trust, eliminate worries, and anxiety and increase the active involvement of the client from one stage to the next.Implication – The implications of this study indicate that cognitive restructuring techniques has an impact on the development of guidance and counseling programs in educational units and can be used as an effort to increase santri self-acceptance. This technique can be used by teachers as caregivers in developing students' self-acceptance in achieving adolescent well-being.Originality - This study strengthens adolescent competence through group counseling that is able to form self-acceptance in students.***Tujuan – Masalah psikologis yang terjadi dapat disebabkan oleh ketidakmampuan untuk memahami dan menerima diri sendiri dengan baik. Tujuan dari penelitian ini adalah untuk menggambarkan secara deskriptif strategi peningkatan penerimaan diri siswa melalui konseling kelompok dengan teknik restrukturisasi kognitifMetode - Menggunakan pendekatan kualitatif, dengan observasi dan wawancara sebagai teknik pengumpulan data. Subjek dipilih dengan menggunakan metode purposive sampling dengan jumlah 8 orang mahasiswa. Analisis dilakukan dengan menggunakan metode interaksi.Hasil  -  Hasil penelitian menunjukkan bahwa peneliti sebagai instrumen kunci menerapkan konseling kelompok melalui teknik restrukturisasi kognitif yang terdiri dari enam tahap: strategi rasionalisasi; mengidentifikasi pikiran negatif; mengenalkan dan melatih pikiran positif; mengalihkan pikiran negatif ke pikiran positif; berlatih memperkuat pernyataan diri (PR); refleksi dan tindak lanjut. Konseling kelompok berusaha membangun hubungan berdasarkan kepercayaan, menghilangkan kekhawatiran, dan kecemasan, serta meningkatkan keterlibatan aktif klien dari satu tahap ke tahap berikutnya.Implikasi – Implikasi dari penelitian ini menunjukkan bahwa teknik restrukturisasi kognitif berdampak pada pengembangan program bimbingan dan konseling di satuan pendidikan dan dapat digunakan sebagai salah satu upaya untuk meningkatkan penerimaan diri santri. Teknik ini dapat digunakan oleh guru sebagai pengasuh dalam mengembangkan penerimaan diri dan well-being santri.Originalitas – Penelitian ini memperkuat kompetensi remaja melalui konseling kelompok dengan teknik restrukturisasi kognitif yang mampu membentuk penerimaan diri pada siswa.